How is Consumer Psychological Well-Being Impacted by Instagram Influencers and Posts in a Female Fitness Culture Context? - Woodward, Katherine Louise (2022)
The issue of Instagram influencers and posts negatively impacting consumers psychological well-being, is a growing problem as the number of Instagram users continue to increase, whilst the issue remains under researched. This dissertation explores how social media and its variables such as outputs from algorithms and influencers impact consumers psychological well-being including self-esteem, anxiety, and depression. Whilst also looking at whether psychological well-being is a superior measure of the impact of Instagram influencers and posts in a female fitness culture context than subjective well-being. A qualitative research method was conducted to provide evidence for this issue. Specifically, in-depth interviews using a semi-structured questionnaire were conducted, which were later coded. Furthermore, this dissertation found that social media, outputs from algorithms, and fitness influencers maintained their negative relationship with self-esteem and anxiety, both worsening, as was deduced from the literature review prior to the interviews. Although, the interviews showed that depression had zero relationship with social media, outputs from algorithms, and influencers, despite propositions deduced from the literature review previously indicating a negative relationship. Additionally, the findings demonstrated that participants were naturally inclined to express their issues with social media with the three psychologically well-being indices, self-esteem, anxiety, and depression, instead of subjective well-being measures such as happiness and life satisfaction. Finally, this dissertation concluded that self-esteem and anxiety were worsened due to pressure from various Instagram trends to have a specific appearance whilst outputs from algorithms caused users to be inundated with curated and filtered content, further worsening both self-esteem and anxiety particularly when referring to body image and comparison. Additionally, depression was not caused amongst those who did not have pre-existing issues with depression as most participants did not deem their low moods severe enough. Whilst it was evident that participants gravitated towards describing their experiences and issues using psychological well-being indices instead of subjective well-being indicators, showing that the adapted Jarman et al. (2021) model (figure 2) is more effective at measuring well-being.